The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.molcel.2010.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2-Dependent Inhibition of the Nuclear Hormone Receptor PPARγ by Cyclic Phosphatidic Acid

Abstract: Summary Cyclic phosphatidic acid (1-acyl-2,3-cyclic-glycerophosphate, CPA), one of nature’s simplest phospholipids, is found in cells from slime mold to humans and has largely unknown function. We find here that CPA is generated in mammalian cells in a stimulus coupled-manner by Phospholipase D2 (PLD2), and binds to and inhibits the nuclear hormone receptor PPARγ with nanomolar affinity and high specificity through stabilizing its interaction with the corepressor SMRT. CPA production inhibits the PPARγ target-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
151
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 32 publications
5
151
0
Order By: Relevance
“…Brief exposure to AGP has been reported to induce progressive neointima formation [10] and, recently, LPA and its analog were shown to stimulate a new type of signaling by directly activating PPARγ [15]. A previous report suggested that neointima formation elicited by unsaturated LPA is not mediated by the LPA receptors (GPCRs) expressed in blood-vessel walls [13]; however, topical application of unsaturated LPA species into the non-injured carotid artery of rodents induced arterial-wall remodeling [13], and this response required PPARγ. LPA and AGP have also been reported to be agonists of PPARγ and have been implicated in atherogenesis [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Brief exposure to AGP has been reported to induce progressive neointima formation [10] and, recently, LPA and its analog were shown to stimulate a new type of signaling by directly activating PPARγ [15]. A previous report suggested that neointima formation elicited by unsaturated LPA is not mediated by the LPA receptors (GPCRs) expressed in blood-vessel walls [13]; however, topical application of unsaturated LPA species into the non-injured carotid artery of rodents induced arterial-wall remodeling [13], and this response required PPARγ. LPA and AGP have also been reported to be agonists of PPARγ and have been implicated in atherogenesis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Binding studies using the PPARγ ligand-binding domain showed that binding study of the AGP was similar to that of the TZD rosiglitazone [16]. We recently identified cyclic phosphatidic acid (cPA) is an endogenous PPARγ antagonist, and it is generated by phospholipase D2 (PLD2) [13]. These observations suggest that activation of PPARγ is likely to lead to a complex cellular response.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…T0070907 was identified as a potent and selective PPAR antagonist and it also inhibited lipid accumulation in 3T3-L1 cells [17]. We have been reported that cPA is a specific and high-affinity antagonist of PPARγ [18] [19] [20]. cPA is a naturally occurring analog of LPA in which the sn-2 hydroxy group forms a 5-membered ring with the sn-3 phosphate [21] [22,23].…”
Section: Introductionmentioning
confidence: 99%